Análisis de causas en la evasión y elusión tributaria de los contribuyentes obligados a llevar contabilidad en la Parroquia Tarqui, Cantón Guayaquil, período 2015 - Moreira Hernández, Ana Miriam (2016)
This research was analyzed tax evasion in its general context, established through bibliographical research, what are the factors affecting the failure by certain taxpayers who choose when to meet their obligations to the state. Establishing mechanisms evasion have certain common features in most countries, within which, taxpayers who make false statements, were found not to issue an invoice for the goods and services they offer, performed by repeatedly substitutive statements, taken expenses that are not covered as deductibles etc. Also many of the factors by which the payment of taxes evaded are: low tax culture, perception of the destination of the resources of the state, the people idiosyncrasies, low risk of being detected, each and every one of these factors increase every day the tax gap, and that is why tax administrations are increasingly committed to seek ways to reduce tax evasion. Controls exercised by the tax authorities of most countries, are focused on combat or decrease the gap evasion and tax avoidance, a situation that has been elucidated for many years as more and more mechanisms by which certain taxpayers opt not to pay in full or decrease taxes. avoidance behaviors such as poor tax culture, the perception of the state in which resources are used and providing a non-transparent tax system, whatever the perception of evading taxpayer will always have the intent to evade payment of taxes.